Persepsi Mahasiswa Kesejahteraan Sosial FISIP USU Terhadap Program MBKM Kampus Mengajar: Stambuk 2020 vs 2021 - Sigalingging, Joy Nikholas Matthew; Asbi, Erni Asneli (Jurnal Intervensi Sosial dan Pembangunan, 2025)
This study aims to analyze the differences in perceptions between Social Welfare students from the 2020 and 2021 cohorts at the Faculty of Social and Political Sciences, Universitas Sumatera Utara, regarding the Merdeka Belajar Kampus Mengajar (MBKM) Teaching Campus program. A quantitative approach with a survey method was used to collect data through questionnaires distributed to samples from both cohorts. The results indicate that 2020 cohort students have a more positive perception of the program compared to 2021 cohort students, primarily due to differences in learning experiences and participation levels in the MBKM program. Students who have participated in the program tend to have a deeper understanding of its practical benefits, such as improved communication skills, leadership, and workplace adaptation. In contrast, students who have not participated rely more on secondary information and peer experiences to shape their perceptions. Another influencing factor is the level of expectation regarding the program's relevance to the field of social welfare. These findings provide valuable insights for the development of the MBKM Teaching Campus program, particularly in designing strategies to increase student participation by considering their academic experience and readiness for the professional world.Keywords:  Perception, Student, Kampus Mengajar, FISIP, KESOS